CLINICAL CHARACTERISTICS, PATHOGENS AND ANTIMICROBIAL SUSCEPTIBILITY OF SPONTANEOUS BACTERIAL PERITONITIS IN CIRRHOTIC PATIENTS AT THE HOSPITAL FOR TROPICAL DISEASES DURING 2022 – 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to describe the clinical, paraclinical characteristics, pathogens, antimicrobial susceptibility of spontaneous bacterial peritonitis in cirrhotic patients.Methods: A descriptive case-series study was conducted on spontaneous bacterial peritonitis patients with cirrhosis upper 16 years old who were treated at the hospital for Tropical Diseases between January 2022 to August 2024.Results: Fever ≥ 38oC was  in 64.6% of patients, followed by abdominal pain (74.6%); 10.5% of patients presented with neither fever nor abdominal pain; 71,8% of patients had white blood cells
Keywords: infection, spontaneous bacterial peritonitis, cirrhosis, Escherichia coli.